Comprehensive Review and Analysis of Cryptography Techniques in Cloud Computing - K. Sasikumar; Sivakumar Nagarajan (IEEE Access)
Cloud computing is a fast-growing industry that offers various online services, including software, computing resources, and databases. Its payment model is usage-based, whereas consistency is based on resource-sharing. Cloud storage is popular among individuals and businesses because it reduces cost, increases productivity, boosts performance, and improves security. However, cloud computing comes with security risks as data are stored with third-party providers, and Internet access limits visibility and control. Effective data security and data protection are key issues compared with traditional on-premise computing. There are several methods for ensuring data security in the cloud, of which cryptography is the most important. Cryptography offers a range of security features including authentication, confidentiality, integrity, and availability. However, a thorough examination of the different cryptography methods in a single study is lacking. This study comprehensively examined different cryptography methods, including deoxyribose nucleic acid (DNA), elliptic curve, homomorphic, hybrid, lightweight, and novel methods. The analysis addresses their methodology, algorithms, results, applications, and limitations and provides valuable suggestions for data security in the cloud. This paper proposes the use of elliptic curve cryptography (ECC) to ensure safe communication and lightweight cryptography for Internet of Things (IoT) devices with limited resources. This emphasizes the benefit of combining asymmetric security with symmetric efficiency in hybrid cryptography.